An invertase inhibitory protein from Pteris deflexa link fronds - Sayago, Jorge Esteban (2001)
Plant invertases play important roles in sucrose metabolism. Cell wall invertase was reported to participate in phloem loading and unloading. Soluble invertases would be involved in hexose level regulation in mature tissues and in stored sucrose utilization within vacuoles. Invertase inhibitory proteins were described as one of the possible mechanisms for invertase activity regulation in some plant species; nevertheless, these proteins were found only in sink tissues, suggesting that this mechanism would not be relevant in the sucrose turnover of leaves. This report describes the purification of invertase from Pteris deflexa fronds and the occurrence of an invertase inhibitory protein in this fern organ, as well as its purification and invertase-inhibitor interactions. The Mr of the invertase and of its inhibitory protein were 90,000 and 18,000, respectively. SDS-PAGE in the presence of 2-mercaptoetanol gave two subunits for the enzyme (Mr=66,000 and 30,000) and only one for the inhibitor. The inhibitor protein is a glycoprotein (12% w/w of neutral sugars) that did not show agglutinating activity like some others, and also showed a high heat stability at pH 5.0. The optimum pH of invertase activity is 5.0, while invertase inhibitory protein caused maximal inhibition at the same pH value. Invertase-inhibitor complex formation occurs in an immediate manner and a protease activity was discarded. The inhibition is non-competitive (Ki=1.5 × 10-6 M) without interactions among the binding sites. The complex is slightly dissociable and sucrose was able to partially reduce the inhibitory effect. Up to the present, invertase inhibitory proteins have been found solely in heterotrophic tissues. In this work we demonstrate that this protein is also present in an autotrophic tissue of a lower vascular plant.